2001
DOI: 10.1128/jcm.39.2.506-508.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma Associated with Previous Human Herpesvirus 8 Infection in Kidney Transplant Recipients

Abstract: This study investigates the prevalence of human herpesvirus 8 (HHV-8) infection in kidney transplant patients, evaluating the risk of HHV-8 transmission via transplantation and the association between pre-and posttransplantation HHV-8 infection and the subsequent development of Kaposi's sarcoma (KS). Immunofluorescence and an enzyme immunoassay were used to determine HHV-8 seroprevalence in 175 patients awaiting kidney transplantation and 215 controls who were attending our clinic for other reasons. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 20 publications
1
58
2
5
Order By: Relevance
“…Other studies have demonstrated that KS occurred rarely after bone marrow transplantation (21); only one case of KS, possibly transmitted by the donor, has been reported in a French cohort (20). In contrast, several studies of HHV-8 infection and KS have been reported after renal transplantation (10,11,16,22,27; Frances et al, letter). In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27).…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies have demonstrated that KS occurred rarely after bone marrow transplantation (21); only one case of KS, possibly transmitted by the donor, has been reported in a French cohort (20). In contrast, several studies of HHV-8 infection and KS have been reported after renal transplantation (10,11,16,22,27; Frances et al, letter). In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27).…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 93%
“…In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27). Notably, KS is clearly more prevalent in the renal transplant population, approaching 4% of transplants (10,11), indicating that the pathogenesis of HHV-8 infection in the two transplant populations is different, which may be related in part to the shorter period of immunosuppression in SCT recipients.…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 99%
“…One study demonstrated that 10 (91%) of 11 kidney or heart transplant patients who developed iatrogenic KS were KSHV positive prior to their procedures (390). Cattani et al calculated a relative risk of 34.4 for kidney recipients who were KSHV seropositive versus seronegative prior to transplant (76). In a transplant cohort in Paris, 8% of 400 kidney transplant recipients were KSHV positive prior to transplantation: 28% of these developed KS within 3 years of their procedures, but none of those who were seronegative prior to receiving the kidney developed KS (165).…”
Section: Iatrogenic Ksmentioning
confidence: 99%
“…12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In particular, PT-KS was primarily observed in kidney recipients ( Figure 1A), whereas lower PT-KS incidences have been recorded in patients receiving other SOTs, mainly liver and heart. PT-KS usually occurs rather early after transplantation (median interval, 30 months), usually as cutaneous or mucosal lesions, whereas visceral involvement occurs in 25%-50% of the cases.…”
Section: Posttransplantation Ks Pel and MCDmentioning
confidence: 99%